2010
DOI: 10.1089/aid.2010.0054
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Distribution of HIV Type 1 Subtypes D and A in Rakai District, Uganda Between 1994 and 2002

Abstract: HIV-1 subtype D (HIV-1D) progresses to disease faster and has lower transmissibility than subtype A (HIV-1A). We examined whether these differences could lead to a population level change in the distribution of these subtypes over time. HIV-1 viral RNA was extracted from stored serum samples from HIV-positive subjects participating in a population-based cohort study in Rakai, Uganda in 1994 and 2002. Portions of the viral proteins gag and gp41 were sequenced and subtyped. HIV-1 subtype assignments were generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 22 publications
5
42
0
Order By: Relevance
“…Therefore, for the purposes of this study, 10 reads or more was the threshold for quality consensus viral sequences (see Fig. S1 in the supplemental material (5). In order to test the intra-and intersubtype viral population sensitivities of our NGS protocol, first-round PCR products targeting the p24 region from these subtype A and subtype D samples were mixed in various ratios, amplified, and sequenced on the Roche 454 system as described above (Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, for the purposes of this study, 10 reads or more was the threshold for quality consensus viral sequences (see Fig. S1 in the supplemental material (5). In order to test the intra-and intersubtype viral population sensitivities of our NGS protocol, first-round PCR products targeting the p24 region from these subtype A and subtype D samples were mixed in various ratios, amplified, and sequenced on the Roche 454 system as described above (Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Over the years, subtype D has been more prevalent than subtype A 4,6,39 however; recent reports from Rakai district in Uganda have shown that the prevalence of subtype A has increased in this region of Uganda. 40 The Rakai study showed a significant decrease in the prevalence of subtype D from 70.2% in 1994 to 62.4% in 2002 and a significant increase of subtype A from 16.7% in 1994 to 23.3% in 2002. The observed changes in subtype prevalence over the years may have several explanations but none is entirely satisfactory.…”
Section: Discussionmentioning
confidence: 96%
“…Accordingly, subtype C is the most prevalent subtype worldwide and subtype A is the predominant subtype in East Africa (2, 3). Furthermore, reports indicate that these subtypes are increasing in prevalence (2,8,9,17).…”
Section: Discussionmentioning
confidence: 99%
“…While there is general agreement that subtype C has a transmissibility rate at least equal to those of other M group subtypes (19,20), some studies have reported increased transmissibility of subtype C compared to subtypes A and D (21)(22)(23). Furthermore, the higher heterosexual transmission of subtype A than of subtype D (24) may have contributed to the expansion of subtype A in Uganda (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation